The Role of Entrepreneurial Motivation in Mediating the Effects of Success, Failure, and Work Quality on Business Sustainability - Dhea Lara Puspita; Suhardi; Rahmad Firdaus (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Micro-businesses, such as Pentol Ceriwis, play a vital role in the local economy, yet their sustainability is often challenged by cycles of success and failure. This study aimed to analyze the influence of business success, business failure, and work quality on entrepreneurial sustainability, with entrepreneurial motivation as a mediating variable. A quantitative approach was employed, utilizing survey data from 100 micro-entrepreneurs within the Pentol Ceriwis network. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that business success and work quality had a significant positive effect on entrepreneurial motivation, while business failure exerted a negative impact. Furthermore, entrepreneurial motivation was proven to significantly mediate the relationship between these independent variables and long-term business sustainability. These findings suggest that maintaining high work quality and psychological motivation is crucial for micro-entrepreneurs to navigate business challenges and ensure longevity.